2020
DOI: 10.3892/ol.2020.12023
|View full text |Cite
|
Sign up to set email alerts
|

Potential relationship between Sirt3 and autophagy in ovarian cancer (Review)

Abstract: Sirtuin 3 (Sirt3) is an important member of the sirtuin protein family. It is a deacetylase that was previously reported to modulate the level of reactive oxygen species (ROS) production and limit the extent of oxidative damage in cellular components. As an important member of the class III type of histone deacetylases, Sirt3 has also been documented to mediate nuclear gene expression, metabolic control, neuroprotection, cell cycle and proliferation. In ovarian cancer (OC), Sirt3 has been reported to regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 115 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Similarly, an increased activation of inflammasome and its contribution to chronic inflammation has been demonstrated in malignant ovarian cancer [ 130 ]. Aging is characterized by ROS-mediated mitochondrial damage, an increase in iron deposition, deregulation of Ca 2+ and postabsorptive plasma cysteine homeostasis, as well as impaired autophagy and sirtuin activity secondary to aberrant insulin receptor signaling; events that are observed also in advanced ovarian cancer [ 131 133 ]. These altered pathways influence progressive increases in intracellular ROS level and oxidative stress [ 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an increased activation of inflammasome and its contribution to chronic inflammation has been demonstrated in malignant ovarian cancer [ 130 ]. Aging is characterized by ROS-mediated mitochondrial damage, an increase in iron deposition, deregulation of Ca 2+ and postabsorptive plasma cysteine homeostasis, as well as impaired autophagy and sirtuin activity secondary to aberrant insulin receptor signaling; events that are observed also in advanced ovarian cancer [ 131 133 ]. These altered pathways influence progressive increases in intracellular ROS level and oxidative stress [ 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al found that Resv could attenuate the oxidative damage of endothelial cells by activating the SIRT3/AMPK pathway to regulate mitochondrial reactive oxygen species homeostasis (Zhou et al, 2014). Moreover, SIRT3 can modulate autophagy in cancer cells (Shi et al, 2020; Wei et al, 2018). Consistent with previous studies, Resv could both activation of SIRT1 and SIRT3, although the effect of SIRT1 on autophagy was unnoticeable.…”
Section: Discussionmentioning
confidence: 99%
“…As a vital member of class III histone deacetylases, SIRT3 mediates nuclear gene expression and cell proliferation. 27 Low expression of SIRT3 contributes to the progression, development, and poor prognosis of human PC. 28 SIRT3 is involved in the carcinogenic activity of miR-708-5p in pancreatic ductal adenocarcinoma cells.…”
Section: Overexpression Of Hif-1α Reversed the Inhibiting Effect Of O...mentioning
confidence: 99%